Self Efficacy dan Financial Behavior Wirausaha Muda Jawa Timur di masa Pandemi Covid-19 - Amidjono, Dwi Sulistyorini (Jurnal Manajemen dan Usahawan Indonesia, 2021)
This study investigated self-efficacy and financial behavior of young entrepreneurs in East Java during the Covid-19 pandemic. Research respondents came from 5,161 young entrepreneurs in East Java with an age range of 18-34 years who took part in Financial Life Skills (FLS) Online Train- ing during June 2020 to April 2021. Data were collected using a questionnaire developed by the YouthWin Through Economic Participation (YEP) project funded by USAID1. The results showed that young entrepreneurs participating in FLS training had slightly higher self-efficacy in financial skills compare to self-efficacy in soft skills, and high financial inclusion behavior with insufficient financial literacy. The findings also revealed a positive, strong, and significant correlation between self-effi- cacy in soft skills and self-efficacy in financial skills; as well as a positive, moderate, and significant corralation between self-efficacy in soft skills and financial behavior related to the attitude towards the importance of understanding financial literacy. To support Indonesian young entrepreneurs, make better, optimal business and financial decisions, they need to be equipped with various self-capacity development programs that combine soft skills with financial skills.